2022
DOI: 10.1371/journal.pone.0266727
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of blood flow in a stenosed artery with post-stenotic dilatation and a forced field

Abstract: Arterial stenosis is a common cardiovascular disease that restricts blood flow. A stenotic blood vessel creates tangent stress pressure, which lessens the arterial side and causes an aneurysm. The primary purpose of this study is to investigate blood flowing via an inclination pipe with stricture and expansion after stricture (widening) underneath the influence of a constant incompressible Casson liquid flowing with the magnetism field. The relations for surface shearing stress, pressure drop, flow resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Future applications of the Galerkin finite element algorithm (G-FEA) could include a range of physical and technological difficulties 11,[50][51][52][53][54][55][56][57][58][59] . According to [60][61][62][63][64][65][66][67][68][69][70] , there have been several recent advancements that explore the importance of the research domain under consideration.…”
Section: Core Points and Conclusionmentioning
confidence: 99%
“…Future applications of the Galerkin finite element algorithm (G-FEA) could include a range of physical and technological difficulties 11,[50][51][52][53][54][55][56][57][58][59] . According to [60][61][62][63][64][65][66][67][68][69][70] , there have been several recent advancements that explore the importance of the research domain under consideration.…”
Section: Core Points and Conclusionmentioning
confidence: 99%
“…Future applications of the G-FEM include a range of physical and technological difficulties [66][67][68][69][70][71][72][73][74][75][76][77]. According to [78][79][80][81][82][83][84][85][86][87], there have been several recent advancements with respect to the importance of the research domain under consideration. The velocity profile can be increased by adjusting the Deborah number (β 2 , β 3 ) and injection parameters, although porous media, volume fraction nanoparticles, velocity slide, and force parameters reduce the speed of the movement.…”
Section: Final Outcomesmentioning
confidence: 99%
“…Future applications of the G-FEM include a range of physical and technological difficulties [66][67][68][69][70][71][72][73][74][75][76][77]. According to [78][79][80][81][82][83][84][85][86][87], there have been several recent advancements with respect to the importance of the research domain under consideration.…”
Section: Final Outcomesmentioning
confidence: 99%
“…For example, a study by Srivastava [48] has shown that a magnetic field can help to reduce the severity of stenosis and improve blood flow. Dhange et al [49] found that MHD may also help to prevent the formation of plaque buildup in arteries. Mohanty et al [50] investigated the impact of heat radiation on the flow of MHD nanofluid over surfaces undergoing both stretching and shrinking.…”
Section: Introductionmentioning
confidence: 99%